Kustomisasi dan Implementasi Odoo ERP: Studi Kasus Perusahaan Manufaktur PT. X - Natanael Kevin Kurniawan S; Yulia Yulia; Eveline Cynthia Irawan (Jurnal Infra, 2022)
Odoo is an open source based ERP application that has various modules that can be configured and customized. In this era of development, information technology has an important role in the business world. PT. X is a manufacturing company that has not utilized information technology to its full potential. This resulted in the emergence of problems in the company, among others: in obtaining information it takes longer time because the data contained in the company has not been integrated. Then, the possibility of human error problems committed by employees, such as forgetting to enter data into the company's data recording. The ERP program was created to try to overcome the problems that occurred at PT. X. For that the platform chosen is Odoo because it has many advantages such as easy to configure and customize the module. To overcome the problems that exist in the company, the development of the Odoo human resources module is carried out. The development of this module will be preceded by designing and analyzing the workflow of the HR division at PT. X. In addition, a review of other laws and regulations related to manpower in Indonesia is also carried out. To measure the success of the implementation of the Odoo ERP program, user satisfaction analysis was carried out using the Doll and Torkzadeh (1998) method. From the analysis of the implementation of the Odoo ERP program in the company, it can be concluded that the Odoo ERP program has a good impact on meeting company needs properly and quickly.